THE FIXATED TRAITS IN “KUNG FU PANDA 3” MOVIE: A PSYCHOANALYTIC LITERARY CRITICISM - Hendrayudo, Dona Widiyanti; Karsum, Annabelle Mathilda Catalunya; Lee, Georgia Love (Jurnal Pendidikan Makarios, 2023)
This study aims to highlight the crucial childhood socio-cultural learning across the lifespan; how the affection, love, close relationships and parenting of both parents are primal that affect adulthood personality. Qualitative method was used to explain and criticize the psychological issue in this movie. Since the story is presented through moving pictures, cameraworks in cinematography were used to narrate the plot, settings, and characters. Furthermore, the theory of “Stages of Psychosocial Development” by Erik Erikson was applied as the approach to conduct this analysis in order to figure out what triggers Po’s anxiety related to two stages of Erikson's Basic Trust vs Mistrust & Autonomy vs Doubt, Shame. As a result: 1) Po’s anxiety is triggered by his inadequate trust at the Basic Trust vs Mistrust stage, making it difficult to control his dietary habit, pessimistic, dependent, and overly sensitive to rejection. 2) The lack of parenting at the Autonomy vs Doubt, Shame stage makes him manifest unfavorable outcomes: a lack of self-control, disorganized, messy and careless behaviors. 3) Po eventually manages to gain his confidence; however, his adult fixation still remains.